Systematic evaluation and kinetic modeling of low heating rate sulfur release in various atmospheres. (1st April 2021) - Debiagi, P.; Yildiz, C.; Ströhle, J.; Epple, B.; Faravelli, T.; Hasse, C.
Abstract: In the present work, a systematic experimental and numerical study of sulfur release from coal in varying atmospheres at low heating rates (LHR) is presented. To this aim, two bituminous coals were investigated, Colombian hard coal (K1) with typical sulfur content, and American high-sulfur coal (U2), with elevated sulfur content. Mass loss and release of target volatile species - H2 S, COS, SO2  - were tracked using a TG-MS. The samples were heated at 10 Kmin −1  under different atmospheres: argon, CO2, synthetic air (21 vol% O2 /79 vol% Ar) and oxy-fuel (21 vol% O2 /79 vol% CO2 ). The role of the different atmospheres in the sulfur release was elucidated as well as the fate of the volatile species in the gas-phase. The advantage of investigating the release at LHR is that heat and mass transfer effects can be neglected, as the experimental conditions allow the process to remain in the kinetic regime. The successive increase in atmosphere complexity allowed to individuate the chemical paths leading to the formation of SOX  and its precursors in each of the conversion steps: devolatilization, char conversion as well as the coupling to gas-phase reactions. The experiments were further analyzed with a kinetic model for the solid-phase of coal conversion, coupled with a detailed gas-phase kinetic mechanism. The solid-phase kinetic model was modified accounting for the particularities of the fuels, for the effects of oxy-fuel atmosphere. A small number of kinetic parameters was adjusted for improved predictions of the release rate and the yields of sulfur species.